2022
DOI: 10.1111/codi.16249
|View full text |Cite
|
Sign up to set email alerts
|

Faecal incontinence is associated with an impaired rectosigmoid brake and improved by sacral neuromodulation

Abstract: Background The rectosigmoid brake, characterised by retrograde cyclic motor patterns on high‐resolution colonic manometry, has been postulated as a contributor to the maintenance of bowel continence. Sacral neuromodulation (SNM) is an effective therapy for faecal incontinence, but its mechanism of action is unclear. This study aims to investigate the colonic motility patterns in the distal colon of patients with faecal incontinence, and how these are modulated by SNM. Methods A high‐resolution fibreoptic colon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…Rectosigmoid dysmotility may be associated with disrupted continence. In a recent HRCM study, a suppressed rectosigmoid brake (i.e., fewer retrograde propagating contractions in the distal colon) was observed in patients with medicallyrefractory faecal incontinence compared to healthy controls (41). While this study was in participants with a native rectum, it is conceivable that a similar attenuation of the rectosigmoid brake may contribute to incontinence and soiling in LARS (41).…”
Section: Pathophysiology Of a Dysregulated Rectosigmoid Brakementioning
confidence: 67%
See 4 more Smart Citations
“…Rectosigmoid dysmotility may be associated with disrupted continence. In a recent HRCM study, a suppressed rectosigmoid brake (i.e., fewer retrograde propagating contractions in the distal colon) was observed in patients with medicallyrefractory faecal incontinence compared to healthy controls (41). While this study was in participants with a native rectum, it is conceivable that a similar attenuation of the rectosigmoid brake may contribute to incontinence and soiling in LARS (41).…”
Section: Pathophysiology Of a Dysregulated Rectosigmoid Brakementioning
confidence: 67%
“…In a recent HRCM study, a suppressed rectosigmoid brake (i.e., fewer retrograde propagating contractions in the distal colon) was observed in patients with medicallyrefractory faecal incontinence compared to healthy controls (41). While this study was in participants with a native rectum, it is conceivable that a similar attenuation of the rectosigmoid brake may contribute to incontinence and soiling in LARS (41). Numerous studies have demonstrated that sacral neuromodulation (SNM), an established and highly successful treatment for faecal incontinence, upregulates retrograde motility of the sigmoid colon, restoring rectosigmoid brake function (41,65,66).…”
Section: Pathophysiology Of a Dysregulated Rectosigmoid Brakementioning
confidence: 93%
See 3 more Smart Citations